55 years of Abacus: Evolution of Research Streams and Future Research Directions. (8th July 2021) - Belloque, Guilherme; Linnenluecke, Martina K; Marrone, Mauricio; Singh, Abhay K; Xue, Rui
Abstract : This article offers a systematic literature review and a bibliometric analysis of articles published over the history of the journal Abacus and marks its 55 th anniversary. The article draws on the latest available bibliometric tools to provide a citation map, burstiness analysis, and further visualization using R Bibliometrix, highlighting highly cited articles and their interrelations across different research streams, as well as trending (or 'hot') topics over the journal's history. We offer reflections on the journal's past and discuss emerging future research directions.